Utilization of wastewater from edible oil industry, turning waste into valuable products: A review. (May 2020) - Ahmad, Talha; Belwal, Tarun; Li, Li; Ramola, Sudipta; Aadil, Rana Muhammad; Abdullah,; Xu, Yanxun; Zisheng, Luo
Abstract: Background: Increased demand of edible oil throughout the world has resulted in establishment of many edible oil industries leading to generation of huge amount of wastewater. Wastewater is generated mostly during the processing operations and washing of equipments. This wastewater has high nutrient content, biological oxygen demand (BOD), chemical oxygen demand (COD), lipids (fats, oil and grease) and organic and inorganic contents, so if disposed untreated it can result in soil, water and air pollution. Scope and approach: This review is aimed to describe different methods used by edible oil industries to treat wastewater and their efficiency for removal of pollution. Especially, focuses on different utilizations of wastewater as a resource from edible oil industry. Key findings and conclusion: Physiochemical (i.e. coagulation/flocculation), biological (i.e aerobic and anaerobic) and electrochemical methods are used for treatment of edible oil industry wastewater. These methods can be used alone or in combination for effective treatment Alternatively, utilization of wastewater is the most recent approach which is not only reduce pollution but also lead to the recovery of useful industrial products, such as bioactive compounds, bioplastic, biofuel, biofertilizer, biopesticide, enzymes, single cell proteins and many more. Moreover, bioactive compounds (i.e. polyphenols) can be extracted and used in different food products which leads to generate potential future possibilities for food and agriculture industries. Highlights: Edible oil industries generates a considerable amount of wastewater. Physiochemical methods can be used as initial process. Wastewater from edible oil industries can be utilized for valuable products. Extracted compounds from wastewater can be used in food products.